Myxozoan parasite diversity in relation to point source pollution using environmental DNA - Sweeney, Emma (2023)
Monitoring freshwater species diversity is essential to understanding the effects that anthropogenic activities have on aquatic environments. Currently, there is limited literature available in relation to the adverse effects of effluent waste on aquatic environments. Parasitic species can act as successful indicators for ecosystem health, as their biodiversity is beneficial to an ecosystem by creating links between trophic levels and increasing species diversity. Environmental DNA (eDNA) metabarcoding is an emerging molecular tool that facilitates non-invasive sampling and detection of communities of species. Myxozoa is an exceptionally large and diverse collective of microscopic obligate cnidarian endoparasites, with multiple waterborne transmission phases, making them ideal subjects for eDNA analysis. Combined sewage overflow sites that overflowed for >100 and <2,500 hours per annum (2020/2021) were selected and 60 (upstream and downstream from CSO) samples were collected from 15 locations during July 2021. A further 30 samples were collected from 15 sites on the river Erewash in July and September 2021. eDNA was extracted from each sample and ideal PCR program was optimised by qPCR for species-specific primers for myxosporeans, malcosporeans and macroinvertebrates and presence of each taxon was confirmed by agarose gel electrophoresis. Amplicons were sequenced on Illumina MiSeq 300bp paired end chemistry in-house at Nottingham DeepSeq facility. Data analysis was conducted using R version 2021.09.0+351 in RStudio version "Ghost Orchid". The results reported in the current study relate only to the two parasite groups, Myxosporea and Malacosporea, as it was found after sequencing that the invertebrate primers yielded insufficient metazoan reads for reliable analyses. The results suggest that the number of individual species of myxosporeans and malacosporeans per site were higher at upstream sites, or sites that received lower levels of pollution throughout the year. From this it can be inferred that there may be a reduction in levels of biodiversity of Myxozoans downstream from CSOs. The current study has demonstrated that it is possible to detect and map diversity of Myxozoan species through eDNA approaches, in relation to environmental stressors such as effluent waste.